Dialogue on Religion, State, and Humanity: A Thought Study of the Scientific Oration Text of a Professor at UIN Syarif Hidayatullah Jakarta - Handayani*, Tuti; Suryani, Rina (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This research aims to 1) describe and analyze the pattern of socio-political and religious thought of professors at UIN Jakarta and 2) exploit the dialogic contribution of the thoughts of UIN professors as intellectuals in building new narratives on religious, social, political, and economic issues. The analytical method used in this study is the Bayani method, a comprehensive explanation of the text and the meaning contained in the discourses big ideas of the discourse. This research paper concludes that there has been a movement and an increase in the pattern of thought of UIN Jakarta professors in interpreting the times and current information. This thought has proven to be successful in providing discourse to the public that the development of Islam is getting bigger, precisely that UIN Jakarta can interpret not only religious scholarship but also contemporary science.